DETECTION OF EXTENDED-SPECTRUM BETA-LACTAMASE PRODUCTION IN GRAM NEGATIVE BACTERIA FROM DIFFERENT CLINICAL ISOLATES - QURSHEED SULTANA,; MAIMOONA MUSTAFA,; HUMERA QUDSIA FATIMA ANSARI, (International Journal of Pharma and Bio Sciences, 2014)
361 gram negative isolates were identified from different clinical specimens (urine, sputum, pus, blood, ET tip, and pleural fluid) collected from patients at two tertiary care hospitals in Hyderabad. The predominant bacterial isolates were Escherichia coli and Klebsiella species. The screening test detected 174(48.19%) of the 361 isolates as potential Extended-spectrum beta-lactamase (ESBL) producers. Out of the 174 isolates which tested positive in the screening test, 137 (38%) were positive in both confirmatory tests, the phenotypic confirmatory combination disc diffusion test and the Epsilometer test, proving that both tests were equally effective. Multidrug resistance was seen in 127 (92.7%) of ESBL positive isolates and 94 (41.9%) of the non ESBL isolates, and the difference was statistically significant (p < 0.01). Because of the high resistance pattern of ESBL producers, it is imperative to detect them in order to overcome therapeutic failures.